Who Controls Campaign Props? Authority and Power in the Election Quiet Period - Dewi, Lia Riesta; Polem, Azmi; Lutfi, M. Uut; Nida, Qotrun; Suriyanti, Lili (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
During the election quiet period, campaign activities, including the use of Campaign Props (APK), are strictly prohibited. This study investigates the authority to regulate and remove APKs during this critical phase. Employing a normative doctrinal research method, the study reveals that Election Participants hold primary responsibility for removing APKs. However, if they fail to comply, Regional Governments are empowered to act, citing the need to maintain public order, cleanliness, and aesthetic standards. Such actions must be coordinated with the Election Commission (KPU) and Election Supervisory Body (Bawaslu) to ensure proper documentation and facilitate sanction recommendations against non-compliant participants. This research highlights the urgent need for clearer regulatory enforcement mechanisms to uphold fairness and order during elections, contributing to the broader discourse on electoral governance and accountability.